2005
DOI: 10.1537/ase.04s017
|View full text |Cite
|
Sign up to set email alerts
|

A Pliocene colobine from the Nakatsu Group, Kanagawa, Japan

Abstract: In 1991, a partial cranium of a fossil colobine monkey was found in Kanagawa Prefecture, Japan. Its geological age is Late Pliocene (ca. 2.5 Ma). It is larger than skulls of living colobine monkeys and resembles a male example of Pliocene Dolichopithecus ruscinensis from France. However, the cranium exhibits some distinctive features, notably very thin postorbital rims (lateral margins of the orbit). Therefore, a new subgeneric and specific name Dolichopithecus (Kanagawapithecus) leptopostorbitalis is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…The same situation has also occurred in Japan, where the oldest fossil monkey is a colobine from the late Pliocene of Kanagawa Prefecture, yet only M. fuscata presently survives there (Iwamoto et al, 2005;Nishimura et al, 2012). The similar evolutionary pattern seen in the two cercopithecid subfamilies of two Far East islands, Taiwan and Japan, could be explained by the global climate change during the Pliocene to Pleistocene in East Asia.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The same situation has also occurred in Japan, where the oldest fossil monkey is a colobine from the late Pliocene of Kanagawa Prefecture, yet only M. fuscata presently survives there (Iwamoto et al, 2005;Nishimura et al, 2012). The similar evolutionary pattern seen in the two cercopithecid subfamilies of two Far East islands, Taiwan and Japan, could be explained by the global climate change during the Pliocene to Pleistocene in East Asia.…”
Section: Discussionmentioning
confidence: 66%
“…Kanagawapithecus is a well-preserved cranial specimen discovered from the late Pliocene of central Japan (Iwamoto et al, 2005). Although it was originally described as a subgenus of Dolichopithecus, the cranial and dental morphology indicates that it is not Dolichopithecus but an independent genus, Kanagawapithecus (Nishimura et al, 2012).…”
Section: Systematicsmentioning
confidence: 99%
“…Kanagawapithecus, another fossil colobine discovered from the Late Pliocene of Kanagawa Prefecture, eastern Japan, has sometimes been considered as a subgenus of Dolichopithecus as well (e.g., Delson, 1994;Iwamoto et al, 2005). However, the reexamination of the inner structure of the Kanagawapithecus skull using X-ray CT demonstrated that it is quite different from the structural pattern seen in Dolichopithecus and Mesopithecus but rather similar to African colobines (Nishimura et al, 2012).…”
Section: Comparisons With Northern Asian Colobine Fossilsmentioning
confidence: 99%
“…Some authorities consider that Dolichopithecus evolved from Mesopithecus by the end of the Miocene (Delson, 1994). Two largesized colobines, Parapresbytis and Kanagawapithecus, discovered from the Middle to Late Pliocene of East Asia (Transbaikalia and Japan, respectively) were once considered to be the subgenera of Dolichopithecus (Borissoglebskaya, 1981;Kalmykov and Maschenko, 1992;Delson, 1994;Iwamoto et al, 2005), but both are now regarded as independent genera, respectively (Jablonski, 2002;Maschenko, 2005;Egi et al, 2007;Takai and Maschenko, 2009;Nishimura et al, 2012). There is another enigmatic colobine tooth from the Early Pliocene that has been discovered in Yushe, Shaangxi Province, northern China, but no detailed descriptions have been published (Delson, 1996;Williams and Holmes, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mesopithecus and Dolichopithecus were widespread throughout Europe and West Asia during the late Miocene and the Pliocene (Figure 1) (Delson, 1994;Fortelius, 2003). In East Asia, Parapresbytis is known from the middle Pliocene of Transbaikalia, Siberia (Borisoglebskaya, 1981;Kalmykov andMaschenko, 1992, 1995), a fossil from the late Pliocene of Japan has been assigned to Dolichopithecus (Delson, 1994;Iwamoto et al, 2005), and Rhinopithecus existed in central China during the Pleistocene (Figure 1) (Jablonski, 2002). The adaptability of cercopithecid monkeys in general, and colobines in particular, has been briefly discussed in Jablonski (2005).…”
Section: Introductionmentioning
confidence: 99%